Physiological Disorders of Landscape Palms - Timothy K. Broschat (EDIS)
Physiological disorders are those caused by various environmental factors, rather than biological agents. Nutrient deficiencies are typically included within this category, but are discussed in other publications See: N deficiency, K deficiency, Mg deficiency, Mn deficiency, Fe deficiency, B deficiency. This document is ENH1011, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date September 2005.